Capital Regulation, Liquidity Requirements and Taxation in a Dynamic Model of Banking - De Nicolo, Gianni (IMF Working Papers; Working Paper ;, 2012)
This paper studies the impact of bank regulation and taxation in a dynamic model with banks exposed to credit and liquidity risk. We find an inverted U-shaped relationship between capital requirements and bank lending, efficiency, and welfare, with their benefits turning into costs beyond a certain requirement threshold. By contrast, liquidity requirements reduce lending, efficiency and welfare significantly. The costs of high capital and liquidity requirements represent a lower bound on the benefits of these regulations in abating systemic risks. On taxation, corporate income taxes generate higher government revenues and entail lower efficiency and welfare costs than taxes on non-deposit liabilities.a.